2021
DOI: 10.3390/su13084261
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Harmonic Resonance Characteristics in Grid-Connected LCL Virtual Synchronous Generator

Abstract: The virtual synchronous generator (VSG), which emulates the essential behavior of the conventional synchronous generator, has attracted great attention. This paper proposes to analyze the harmonic resonance characteristics in VSG using the state-space model. The analysis is based on a full-order state-space small-signal model that fully considers the dynamic of the inner loops and the VSG-based outer power control loop. Participation analysis is used to point out the contributions of different states to the ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To improve the stability and stability margin of the PV generation and ES system, Milano et al [9] and Jiang et al [13] employed the root locus method to analyze the impact of control parameter variations on system stability. However, root locus-based parameter optimization methods often exhibit subjectivity and lack well-defined, scientifically quantifiable design criteria.…”
Section: Parameter Optimization Design For Gfm Pv Es System Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the stability and stability margin of the PV generation and ES system, Milano et al [9] and Jiang et al [13] employed the root locus method to analyze the impact of control parameter variations on system stability. However, root locus-based parameter optimization methods often exhibit subjectivity and lack well-defined, scientifically quantifiable design criteria.…”
Section: Parameter Optimization Design For Gfm Pv Es System Parametersmentioning
confidence: 99%
“…[12] suggested that when a single VSG is connected to the grid, if the line resistance and reactance are of similar magnitudes, active and reactive power become coupled, leading to oscillations. Jiang et al [13] used a state-space model to analyze the influence of inner loop proportional gain, integral coefficient, and virtual inductance parameters on harmonic oscillation characteristics. Xu et al [14,15] improved dynamic characteristics by adding a differential loop in the VSG power loop but introduced high-frequency interference, affecting calculation accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…While all VSG strategies control active and reactive power, each has its control frame. Furthermore, different VSG control strategies have been introduced to enable the inverter to emulate the properties of an SG [41,52]. As a result, every VSG implementation entails an approximately direct mathematical model of an SG [4].…”
Section: Vsg Conceptmentioning
confidence: 99%
“…Furthermore, to approximate the electromagnetic properties of SG for VSG, the SG's stator equation is usually simulated without considering the electromagnetic relationship between rotor and stator, and this can be expressed as [52]:…”
Section: Vsg Conceptmentioning
confidence: 99%
See 1 more Smart Citation